Die kerklike stimulasie van eietydse transformasieprosesse, en die geleentheid wat dít aan nywerheidsbediening bied - Müller, Michau (HTS teologiese studies, 2010)
The stimulation of the modern transformation processes by the church and the opportunity this presents to industrial mission The church had reacted to both political and industrial change. Localised theology was the answer to a restricted political dispensation, and the final result was the application of liberation theology. The Kairos Document, the Evangelical Witness, the Belhar Confession and Church and Society express the different churches’ viewpoints about the apartheid regime. This contextual focus on the same political dispensation unleashed church influence during the establishment of a national democratic dispensation. The different efforts to deal with industrial change by means of church renewal have finally paved the way for the development of a new industrial mission, vision and approach. This has resulted in the forming of an interchurch industrial organisation, and far-reaching possibilities within the industrial environment.